Association between Single Nucleotide Polymorphisms in XRCC3 and Radiation-Induced Adverse Effects on Normal Tissue: A Meta-Analysis. - Yu-Zhe Song (PLoS ONE, 2015)
The X-ray repair cross-complementing group 3 (XRCC3) protein plays an important role in the repair of DNA double-strand breaks. The relationship between XRCC3 polymorphisms and the risk of radiation-induced adverse effects on normal tissue remains inconclusive. Thus, we performed a meta-analysis to elucidate the association between XRCC3 polymorphisms and radiation-induced adverse effects on normal tissue. All eligible studies up to December 2014 were identified through a search of the PubMed, Embase and Web of Science databases. Seventeen studies involving 656 cases and 2193 controls were ultimately included in this meta-analysis. The pooled odds ratios (ORs) with corresponding 95% confidence intervals (CIs) were calculated to evaluate the association between XRCC3 polymorphisms and the risk of radiation-induced normal tissue adverse effects. We found that the XRCC3 p.Thr241Met (rs861539) polymorphism was significantly associated with early adverse effects induced by radiotherapy (OR = 1.99, 95%CI: 1.31-3.01, P = 0.001). A positive association lacking statistical significance with late adverse effects was also identified (OR = 1.28, 95%CI: 0.97-1.68, P = 0.08). In addition, the rs861539 polymorphism was significantly correlated with a higher risk of adverse effects induced by head and neck area irradiation (OR = 2.41, 95%CI: 1.49-3.89, p = 0.0003) and breast irradiation (OR = 1.41, 95%CI: 1.02-1.95, p = 0.04), whereas the correlation was not significant for lung irradiation or pelvic irradiation. Furthermore, XRCC3 rs1799794 polymorphism may have a protective effect against late adverse effects induced by radiotherapy (OR = 0.47, 95%CI: 0.26-0.86, P = 0.01). Well-designed large-scale clinical studies are required to further validate our results.